The association ofApoCIII, beta-3 adrenegic receptor and TNF-ailpha polymorphisms with lipodystrophy in HIV positive patients receiving antiretroviral therapy - Tlomatsana, Tebatjo Francis (My University, 2016)
Ever since the introduction of highly active antiretroviral therapy (HAART), body profile changes and metabolic anomalies have increasingly been witnessed in HIV-positive patients. Lipodystrophy which is characterized by lipoatrophy and lipohypertrophy is one of the most noticeable conditions. The aim of this study was to determine the possible association of ApoCIII, beta-3 adrenergic receptor and TNF-alpha gene polymorphisms with the presence of lipodystrophy in the HIV positive subjects on HAART. HIV-positive subjects (n= 209) were recruited from Helen Joseph Hospital and Charlotte Maxeke Johannesburg Academic Hospital. Control group of HIV-negative subjects (n=100) were also recruited for the study. Lipodystrophy was identified through patient self-assessments on changes in body fat using a questionnaire. Anthropometric data was recorded and genomic DNA extracted. A PCR-based RFLP technique was used to screen for ApoCIII (-T455C and -C482T), beta-3 adrenegic (-T64A) and TNF-alpha (-G238A and -G308A) gene polymorphisms. Lipodystrophy was detected in 27% of the HIV positive subjects and was characterized by lower mean weight (62.5 ± 11.1) compared to subjects without lipodystrophy (67.6 ± 12.9; p<0.05).The frequency for the TNF-alpha variant allele, –308A was significantly higher in individuals with lipodystrophy (25%) compared to those without lipodystrophy (13%; p<0.05). The allele frequencies for the ApoCIII, beta-3 adrenergic receptor and TNF alpha -238 polymorphisms were similar between patients with and without lipodystrophy. Lipodystrophy in this patient cohort is characterized by lipoatrophy and the presence of the variant A allele at the TNF alpha -308 locus.
A dissertation submitted to the Faculty of Health Science, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Science in Medicine. Johannesburg, September 2015